COVID‐19 in cancer patients on active systemic therapy – Outcomes from LMIC scenario with an emphasis on need for active treatment. (31st October 2020) - Ramaswamy, Anant; Nayak, Lingaraj; Roy Moulik, Nirmalya; Sengar, Manju; Chinnaswamy, Girish; Jobanputra, Kunal; Shah, Minit J.; Kapoor, Akhil; Joshi, Amit; Kumar, Amit; Gokarn, Anant; Bonda, Avinash; et al.
Abstract: Background: There is limited data on outcomes in cancer patients with coronavirus disease 2019 (COVID‐19) from lower middle‐income countries (LMICs). Patients and Methods: This was an observational study, conducted between 12 April and 10 June 2020 at Tata Memorial centre, Mumbai, in cancer patients undergoing systemic therapy with laboratory confirmed COVID‐19. The objectives were to evaluate cumulative 30‐day all‐cause mortality, COVID‐19 attributable mortality, factors predicting mortality, and time to viral negativity after initial diagnosis. Results: Of the 24 660 footfalls and 7043 patients evaluated, 230 patients on active systemic therapy with a median age of 42 (1‐75) years were included. COVID‐19 infection severity, as per WHO criteria, was mild, moderate, and severe in 195 (85%), 11 (5%), and 24 (11%) patients, respectively. Twenty‐three patients (10%) expired during follow‐up, with COVID‐19 attributable mortality seen in 15 patients (6.5%). There were no mortalities in the pediatric cohort of 31 (14%) patients. Advanced stage cancer being treated with palliative intent vs others [30‐day mortality 24%% vs 5%, odds ratio (OR) 5.6, 95% CI 2.28‐13.78, P  < .001], uncontrolled cancer status vs controlled cancer (30‐day mortality37.5%% vs 4%%, OR 14, 95% CI 4.46‐44.16, P  < .001) and severe COVID‐19 vs mild COVID‐19 (30‐day mortality 71% vs 3%, OR 92.29, 95% CI 26.43‐322.21, P  < .001) were significantly associated with mortality. The median time to SARS‐CoV‐2 RT‐PCR negativity was 17 days [interquartile range (IQR)17‐28) in the cohort. Conclusions: The mortality rates in cancer patients with COVID‐19 who are receiving systemic anti‐cancer therapy in LMICSs are marginally higher than that reported in unselected COVID‐19 cohorts with prolonged time to viral negativity in a substantial number of patients. The pediatric cancer patients tended to have favorable outcomes. Abstract : COVID‐19 attributable mortality in cancer patients on systemic therapy in LMICs appears lower than published data and slightly more than an unselected patient's cohort. Delayed recovery in terms of SARS COV‐2 negativity is seen in these patients. Treating Cancer remains the priority.